Implementasi Penggunaan Load Cell pada Mesin Peniris Minyak untuk Keripik Usus - Adimi, Akbar Roisul; Fauziyah, Mila; Dewatama, Denda (Program Studi Teknik Elektronika Politeknik Negeri Malang, 2024)
Chicken ntestinal chips are processed foods that are often found in the general public. Intestinal chips are also an innovation from the community that processes waste from slaughtering chicken, namely intestines, into processed food. Processing of chicken intestinal chips determines the yield of these products so that chips can be produced which have a good shape and are not crushed, have a pleasant aroma, good taste, and have a brownish yellow and crunchy color. The process of making intestinal chips goes through several processes, one of which is the process of draining the oil. In the process of draining oil from intestinal chips it takes a long time. To shorten the time, an oil slicing machine is needed so that it does not require a long time but manual slicing can also be done. Drain speed control using the PID method. This method is expected to maintain the stability of the draining cycle. The results of the test obtained the value of Kp = 6, Ki = 2, Kd = 3 at the stirring speed control with a set point of 1400 RPM with the response results namely rise time of 16 s, delay time of 4 s, settling time of 66.5 s, Mp of 1.95%, peak time of 15.5 s, ESS of 1.95% and -2.25%.